A Cardio pulmonary resuscitation device for stretchers - Sadani, Kapil; A.P. Prabhakar, D; Nag, Pooja (International Journal of Engineering and Technology, 2018)
Cardiopulmonary Resuscitation (CPR) machine is a class III medical device for use in cardiac arrests. This budget device has been fabricated in house and calibrated using data from sensors used when an expert administers CPR on a patient in the face of emergency. Also, the device has its own feedback sensorics to optimize CPR delivery primarily the full chest recoil. The device was tested on mannequin and its performance was identical to trained CPR experts in terms of rate and pressure. On fulfilling all ethical requirements, this device has the potential to be a life saver in India and worldwide.Â